FOLKLORE, FABLES, AND THE FUSION OF POLITICS, CULTURE, AND CHARACTERS IN VALLI BY SHEELA TOMY - Varghese, Gifty Elza (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present-day folkloristic research in India has attracted lots of adhesions mainly through the works of the emergent Indian folklorist. Still, the wider circle of academia remains uninspired by this field. The representative case study is offered by the novel Valli by Sheela Tomy, demonstrating the three-dimensionality of folklore and deep-seated cult nature. The word ‘Valli’ itself carries multiple meanings: climbing plant, earth, young woman, and even a feudal-age measure of paddy issued as wages. The richness of folkloric interpretations is well-supported by this novel, as it presents the Wayanad region’s sociopolitical turbulence arising from political rivalries, religious conflicts, linguistic differences, and indigenous traditions. Through the story of strong-willed characters that fight to preserve their heritage, Valli showcases the continued importance of folklore in studying and preserving Wayanad culture. This paper aims to examine the folkloric components within Valli and analyze the role they play in preserving the regional cultural identity.